The hermeneutical approach in translation studies - Stefanink, Bernd; Bălăcescu, Ioana (Manuscrítica: Revista de Crítica Genética, 2021)
Our aim is to convince the reader of the validity of hermeneutical approach in translation studies. In a first part, we will show that this validity is based on the fact that the hermeneutical approach integrates factors like subjectivity, intuition, corporeality and creativity in its theoretical reflection, being thus close to the reality of the translator. In a second part, we will situate this approach in the context of the development of modern translation studies since the 1950s, and show that this development was characterized by a dominating tendency that led from an atomistic to a more holistic view of the translation unit, legitimating the holistic approach, which is fundamental in translational hermeneutics. Our third part relates the history of philosophical hermeneutics as the legitimate foundation of translational hermeneutics. In a fourth part, devoted to the "outcoming perspectives", we will try reinforce the legitimacy of the hermeneutical approach by showing how it is supported by recent results of research in cognitive science. In order to foster further research in translational hermeneutics we also offer a methodology based on hermeneutic principles to study the translation process. Finally, we give an example of legitimation of a creative problem-solving, based on a hermeneutical approach of a translation problem which finds its validation in the results of cognitive research.